2018
DOI: 10.1001/jamacardio.2018.3789
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Signaling in Next-Generation Pharmacotherapies for Heart Failure

Abstract: Key PointsQuestionHas the time arrived for new heart failure therapeutic pathways over and above receptor antagonism to be considered?FindingsThis review identified that regulating angiotensin II receptor activation as well as activation of specific receptor pathways can provide favorable cardiovascular effects in the context of heart failure, which cannot be achieved by receptor inhibition alone.MeaningThe positive results of the PARADIGM-HF trial using a drug with both neutral endopeptidase and angiotensin I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 174 publications
0
11
0
Order By: Relevance
“…A similar dynamic course could be confirmed with our data. However, NEP cleaves a broad spectrum of peptides; thus, it was suggested that the net effect of NEPi would be more complex depending on the relative dominance of the respective substrates 14 . The affinity of NEP to ADM is assumedly even higher than to BNP 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar dynamic course could be confirmed with our data. However, NEP cleaves a broad spectrum of peptides; thus, it was suggested that the net effect of NEPi would be more complex depending on the relative dominance of the respective substrates 14 . The affinity of NEP to ADM is assumedly even higher than to BNP 15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, NEP cleaves a broad spectrum of peptides; thus, it was suggested that the net effect of NEPi would be more complex depending on the relative dominance of the respective substrates. 14 The affinity of NEP to ADM is assumedly even higher than to BNP. 15 While BNP increased by 20% from baseline levels in the PARADIGM-HF cohort, 13 concentrations of bio-ADM and MR-proADM nearly doubled and remained stable over 2 years after the initiation of ARNi in our study.…”
Section: T a B L E 2 Correlation Between Bio-adm Mrmentioning
confidence: 99%
“…Recently, an effective new heart failure drug was developed in which the ARB valsartan was combined with the neprilysin inhibitor sacubitril (21), which blocks the degradation of endogenous natriuretic peptides, leading to an increase in cyclic nucleotides in target tissues, particularly in the kidney (15). The combination of these two drugs proved to be more efficacious than RAAS blockade alone in preventing the progression of heart failure (21,25). Although the effects of AT1R blockade on the vasculature have long been appreciated, the roles of cardiac AT1Rs in development of heart failure are much less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…NEP is a transmembrane zink‐dependent metallopeptidase and is implicated in the degradation of numerous peptides with varying substrate selectivity 18 . Several potential bioactive signalling pathway candidates have been identified including enkephalins and substance P 19 …”
Section: Discussionmentioning
confidence: 99%
“…NEP is a transmembrane zink-dependent metallopeptidase and is implicated in the degradation of numerous peptides with varying substrate selectivity. 18 Several potential bioactive signalling pathway candidates have been identified including enkephalins and substance P. 19 The primary hypothesis for the mechanism of action of NEPi in HFrEF specifically is to increase endogenous NP levels by blocking their inactivation. 18,20 A modest increase in BNP at short term after therapy initiation has been shown.…”
Section: Mechanism Of Action Of Neprilysin Inhibition As the Novel Therapeutic Approach In Heart Failurementioning
confidence: 99%